Misleading “non‑rasayanas” - Kukkupuni, Subrahmanya Kumar; Narayanan, Venugopalan Somavilasome (Pharmacognosy Reviews)
The idea of “non‑rasayanas” put forward by Gaurav Mahesh Doshi and co‑authors[1] does not exist in Ayurveda at the first instance. Though, in science, it is always welcome to generate new ideas, concepts, and terminologies, one must take sufficient care while conceptualizing them. Authors must define the scope of new concept/word with adequate clarity, supported by evidence. The concept/word “non‑rasayana” proposed by them is very immature and not substantiated with evidences in the article. The theoretical background to consider an herb as non‑rasayana has not been mentioned anywhere in the article. However, it appears that the authors are targeting exploration of herbs not described as rasayana in Ayurveda, but have a potential to bring about immunomodulation as non‑rasayana.